Wound scabs protect regenerating tissue against harmful ultraviolet radiation - van der Pol, E.; Mudde, Y.D.; Coumans, F.A.W.; van Leeuwen, T.G.; Sturk, A.; Nieuwland, R. (Medical hypotheses, 2016)
Benefits attributed to wound scabs include prevention of blood loss and protection against infection. However, when formation of a wound scab is prevented, the risk of infection is reduced. Moreover, in the absence of a wound scab, wounds heal faster and scar formation is reduced. The question arises why we develop a wound scab. Here we show that wound scabs inhibit transmission of ultraviolet radiation (UVR). We compared the UVR transmittance of human wound scabs to sunscreen by measuring the sun protection factor (SPF) with diffuse transmittance spectroscopy. Three wound scabs showed SPFs of 70, 84, and 300, which is more effective than the most protective commercially available sun block. Because our results demonstrate that a wound scab offers natural protection against UVR, and because no beneficial trait is attributed to wound scabs, we hypothesize that the main function of wound scabs is to limit DNA damage in underlying cells during regeneration of wound tissue exposed to sunlight, thereby reducing the risk of developing skin cancer.